FUNGSI PUBLIC RELATION PT PLAZA INDONESIA REALTY, TBK DALAM MEMPERTAHANKAN POSITIONING PLAZA INDONESIA MELALUI KEGIATAN MEDIA RELATIONS - Selvya Hutabarat (Communication, 2012)
The purpose of this study was to determine the function of Public Relations in PT Plaza Indonesia Realty Tbk. This study in constructivist paradigm, with a qualitative approach. Data collection with primary and secondary data. Primary Data with in-depth interviews and observation, while the secondary of data from the literature is to get media, online and so on. His study is PT Plaza Indonesia Realty Tbk. has succeeded in establishing the Public Relations functions to achieve the objectives in order to maintain the positioning Plaza Indonesia. Meanwhile, Public Relations, which is seconded by one person Public Relations Assistant can also be said to have been successful in implementing the specified function of the company through one of the ways that media relations activities, which the Public Relations, Supervisor has been working with the smart in taking the strategic benefits of such activities as efforts to confront and overcome the dynamism in the business competition.